Inhibition of pentagastrin-stimulated acid secretion after subcutaneous administration of a new somatostatin analogue. Issue 2 (February 1986) - Whitehouse, I; Beglinger, C; Rüttimann, G; Gyr, K
Abstract : Somatostatin, a peptide present in hypothalamus, gastric mucosa, and pancreas suppresses several gastrointestinal functions. Its short half life has prevented clinical use. We have therefore evaluated the effect of subcutaneous administration of a new synthetic somatostatin analogue, in comparison with a placebo, on pentagastrin stimulated acid secretion in six healthy volunteers. On different days, acid secretion was measured continuously, after a basal 30 minutes, for six hours during 3 micrograms/kg/h of intravenous pentagastrin. Acid secretion was measured with a marker technique (0.1% phenol red) to correct for duodenal volume loss. Blood was drawn in regular intervals to measure plasma somatostatin concentrations by radio immunoassay. One hour after starting the pentagastrin infusion, a single subcutaneous injection of either 100 micrograms somatostatin analogue, or placebo (isotonic saline) was given. In a follow up study, somatostatin was given subcutaneously in a dose of 200 micrograms. No difference in efficacy was observed between the two doses. A single subcutaneous injection of the somatostatin analogue significantly suppressed acid secretion for five hours (p less than 0.01). Maximal inhibition was approximately 75%. Mean elimination half life of the analogue was approximately 80 minutes. We suggest that the new somatostatin analogue might be useful for clinical use.